The Politicization of Aid in the Electoral Process in Banda Aceh - Fajri, Nurul; Susilawati, Novi; Helmi, Helmi; Fajri, Raihal (Electronic Journal of Education, Social Economics and Technology, 2024)
This study examines the politicization of aid in the 2024 Legislative Election in Banda Aceh through the lens of patron-client theory, exploring how candidates or political parties use material aid to secure electoral support. Using a qualitative descriptive method, data were collected through interviews with voters in Banda Aceh and a review of relevant literature. The findings reveal that material aid often functions as a transactional tool, with voters expected to reciprocate by voting for the candidates providing assistance. This reciprocal expectation significantly influences voter behavior, as many prioritize immediate material benefits over ideological or programmatic considerations. However, not all voters adhere to this transactional dynamic; some evaluate candidates based on their political qualities and programs, regardless of aid. Perceptions of candidates who abstain from providing aid vary—some voters see the absence of aid as a disadvantage, while others value the candidates' vision and integrity over material offerings. The study concludes that while aid politicization impacts electoral outcomes, maintaining voter trust and loyalty depends on candidates' fulfillment of political promises and long-term commitment. Balancing short-term aid strategies with genuine political accountability is essential for sustaining trust and upholding the integrity of the political system.